Type and storage of human remains detection canine training aids: A review and handler survey - Fantasia Whaley; Daigoro Greco; Kaitlyn Mercando; Rushali Dargan; Lauryn DeGreeff (Forensic Science International: Synergy, 2025)
When properly trained, canines are very effective detectors, especially in human remains detection (HRD) and search and rescue (SAR). However, the variability in decomposition odor profiles presents a challenge and requires extensive and adaptable training. Although some protocols and guidelines exist, they do not account for all the possible influential factors leading to inconsistency between organizations. This paper combines a review of research on factors affecting the odor profile of remains with a survey of canine training in the field. Key aspects covered include training aid materials used (e.g. bones, blood, body parts), sample age, containment material, and storage conditions. Findings reveal a consensus amongst handlers and research in some practices, such as use of multiple training aid materials for a variation in odor profiles and use of glass containment to minimize background odor. Discrepancies, however, remain, particularly in the age of sample (fresh vs. very aged), frequency of aid replacement, and storage conditions such as temperature and humidity. The results emphasize the importance of exposing canines to diverse remains odors in differing conditions, providing recommendations for more improved HRD training and directions of future research.